PENGARUH PROMOSI, E-WORD OF MOUTH DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK MS. GLOW LUMAJANG21 - Rosita, Rurry Eka; Setianingsih, Wahyu Eko; Reskiputri, Tatid Diansari (Relawan Jurnal Indonesia, 2022)
This study aims to examine and analyze the role of Promotion, E-word Of Mouth and Brand Image on product purchasing decisions of Ms. Glow Lumajang21. The type of data in this study used quantitative data in the form of an online questionnaire. The population in this study were all consumers who shopped at Ms. Glow Lumajang21 which is unlimited in number. The sample used in this study were 105 respondents with a non-probability sampling technique. Data collection techniques include primary data and secondary data. The data measurement technique uses a Likert scale. The analytical tool in this study uses multiple linear regression analysis which is supported by instrument testing, classical assumption test and hypothesis testing. The results of this study prove that promotion has a positive and significant effect on purchasing decisions for Ms. Glow Lumajang21 with a significance level of 0.002 <0.05 with a coefficient of 0.613. E-word Of Mouth has a positive and significant effect on product purchase decisions Ms. Glow Lumajang21 with a significance level of 0.001 <0.05 with a coefficient of 0.535. And Brand Image has a positive and significant effect on product purchase decisions Ms. Glow Lumajang21 with a significance level of 0.023 <0.05 with a coefficient of 0.453.